Praying Together as Habitual Action to Shape the Akhlak of Students - Surahyo (Journal of Research in Islamic Education, 2022)
The purpose of this study is to describe the guidance of the morality of the students of Muhammadiyah high school through habituation prayer. This research method uses qualitative. The results of this study indicate that the efforts of Islamic Religious Education teachers in applying the habit of praying in congregation at school with the aim of forming morality students of South Bengkulu Muhammadiyah High School, namely by showing morals and good behavior, speaking softly, neatness in dressing, disciplined learning and respecting teachers and fellow teachers friend. All of this is the active role of schools or Islamic religious education teachers who instill religious values in students. The behavior of Muhammadiyah high school students currently shows the success of the role of Islamic Religious Education teachers in fostering the morals of students although not entirely is the achievement of teachers in fostering the morals of students, but there are several important factors that support the morals of students such as the awareness of parents to always supervise their children, activities religion around the neighborhood or outside the school environment, and good relationships